THE BACKWASH EFFECT OF THE NEW HSK LEVEL 4 TEST ON THE TEACHING OF CHINESE BY THAI NATIVE CHINESE TEACHERS - LAOTRAKUNCHAI, KIRATAYA (Chinese Language and Culture Journal, 2020)
This article uses a questionnaire method in quantitative research to investigate the local Chinese teachers in Thailand. It investigate the backwash effect of the new HSK Level 4 test on the teaching of Chinese by Thai native Chinese teachers and explores the attitude and influence of Thai native Chinese teachers on the new HSK Level 4 exam. The results show that the backwash effect of the new HSK Level 4 test on the teaching of Chinese by Thai native Chinese teachers is more positive than negative. Based on this, the article puts forward the enlightenment and suggestions for the new HSK Level 4 test for Chinese language teaching by local Chinese teachers in Thailand.